Cost and Benefits of Ecosystem Based Adaptation: The Case of the Philippines - Baig, Saima Pervaiz (Archīum Ateneo, 2015)
As the world moves towards conservation goals, such as the Aichi Biodiversity Targets and the Sustainable Development Goals, it is with the undeniable knowledge that climate change is impacting both people and nature adversely by exacerbating existing threats and posing new risks. In light of this, varied adaptation approaches are being promoted and implemented to enable communities and ecosystems deal with the adverse impacts of climate change. One such approach is Ecosystem based Adaptation (EbA). This approach is an excellent example of an effective nature-based solution to climate change, as it uses both biodiversity and ecosystems as part of a larger adaptation strategy. It not only provides climate change adaptation benefits, but also contributes to biodiversity conservation and to enhancing local economies. IUCN has been extensively involved in EbA work, strengthening community resilience and livelihoods in almost 60 countries. This work demonstrates our ongoing commitment to the implementation of nature-based solutions. To further promote the implementation of EbA approaches and to gather evidence from the field, IUCN spearheaded a previous study to identify the economic costs and benefits associated with EbA in a number of countries. As a second phase, this study concentrates on showcasing examples of cost benefit analyses specifically from the Philippines. The lessons learned from this appraisal process will make it easier for policy makers to compare EbA options with engineered solutions. The study, which was carried out with the financial support of the French Government, reviewed projects and assessed existing data from two sites in the Philippines. It highlights that undertaking economic costs and benefits of EbA options is important for decision and policy making purposes. The examples show that in many cases nature based solutions provide more economic benefits than engineering solutions in the long run, especially when co-benefits are considered. For example, in one case mangrove protection provided avoided damages for shoreline protection of USD 206,621, as compared to building a seawall, which provided avoided damages of USD 180,046 with a 10% discount rate. Furthermore, mangrove ecosystems provide additional benefits through fisheries contributing USD 174,000 annually to local community. Such analyses encourage discussion on the viability of EbA approaches in dealing with climate change as well as their contribution to societies and economies. IUCN is very grateful to the French Ministry of Foreign Affairs and International Development (Ministère des Affaires Etrangères et du Développement International) for the financial support that made this important study possible. This, IUCN hopes, will act as an incentive for other EbA projects to ensure that they carry out such analyses and further enhance the case for naturebased solutions. Inger Andersen IUCN Director General January, 2016